Analysis of Sharia Financing Potentials on Fisheries Sector - Assany, Muhfiatun (Institut Agama Islam Negeri Surakarta, 2018)
The purpose of this research is to find out the potency of sharia financing in the fisheries sector in Jetis Village, Nusawungu, Cilacap District. The study was conducted in Jetis Village, Nusawungu, Cilacap District, with the consideration that Jetis Village is the village with the most businesses in the field of fisheries. The sample in this research is fisherman and businessman processed Lea Fish Chips (Krispi Ikan Lea). The data in this research is collected with interview technique. The data analysis used in this research is qualitative and quantitative analysis. The qualitative analysis is used to get an overview of descriptive explanation regarding the fisheries industries. Meanwhile, the quantitative analysis is used for analyzing the cost of every activity, such as investment cost, operational cost, production and marketing cost. Financial analysis is also used to measure cash flow, Break Event Point, Payback Period, Net Present Value and sensitivity analysis. The finding of this research shows that the fisheries business in Jetis Village has the potency to get financing from Islamic Banking. Based on the analysis of the financial feasibility of the lea crispy sich (Krispi Ikan Lea) business is feasible to be cultivated. With a five year project period and 20,6% of margin rates, this business could pay their payment to the Islamic Bank dan produce a good amount of profit for their business. The fishermen also passed the financial feasibility test and are also cultivated with a five-year period of the project and with a total profit of Rp 121,245,775.